Emphysematous Pyelonephritis: Successfully Managed with Conventional Approach - Samad, Tabassum; Haque, Wasim Md Mohosin Ul; Rahim, Muhammad Abdur; Rahim, MA; Iqbal, Sarwar (Bangladesh Journal of Medicine, 2016)
Emphysematous pyelonephritis is a rare necrotizing renal parenchymal infection characterized by gas accumulation in kidneys with or without involving surrounding structures. Patients with diabetes mellitus are the usual sufferers. Here we depict a case of a young Bangladeshi diabetic lady who presented with abdominal pain and dysuria. Investigations confirmed left sided emphysematous pyelonephritis. She responded well to open drainage along with antibiotic coverage. Bangladesh J Medicine Jul 2016; 27(2) : 78-80